2019
DOI: 10.17051/ilkonline.2019.562062
|View full text |Cite
|
Sign up to set email alerts
|

Zihin Engelliler Öğretmen Adaylarının Öğretmenlik Uygulaması Dersine ve Uygulama Okullarına İlişkin Beklentilerinin Belirlenmesi

Abstract: Öz. Bu çalışmanın amacı, özel eğitim öğretmen adaylarının Öğretmenlik Uygulaması dersine ve dersin yürütüldüğü uygulama okullarına ilişkin beklentilerinin belirlenmesidir. Çalışmada durum çalışması deseni kullanılmıştır. Çalışmaya, zihin engeliler öğretmenliği programına devam eden ve Öğretmenlik Uygulaması I dersini alan 75 özel eğitim öğretmen adayı katılmıştır. Veriler, açık-uçlu sorulardan oluşmuş, yarı-yapılandırılmış bir görüşme formu kullanılarak toplanmıştır. Verilerin analizinde içerik analiz kullanıl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…In addition, it was stated by the students that the practice kit used during the special education teaching practice is appropriate in its current form. There were no findings regarding the lack of time (Yücesoy-Özkan et al, 2019). The finding that the practice kit obtained in this study has planning and feedback functions is similar to the finding of Yücesoy-Özkan et al ( 2019) that the practice kit facilitates the planning and implementation of teaching methods and techniques.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In addition, it was stated by the students that the practice kit used during the special education teaching practice is appropriate in its current form. There were no findings regarding the lack of time (Yücesoy-Özkan et al, 2019). The finding that the practice kit obtained in this study has planning and feedback functions is similar to the finding of Yücesoy-Özkan et al ( 2019) that the practice kit facilitates the planning and implementation of teaching methods and techniques.…”
Section: Discussionsupporting
confidence: 86%
“…The findings regarding the roles assumed by the research assistants during the implementation process indicate that there are differences among the research assistants in terms of conducting and grading the teaching practicum and that their opinions were not considered in the creation and execution of the content of the teaching practicum course; however, conducting the course contributed to their professional development by teaching them skills such as making quick decisions, taking the initiative, and collaborating with others. In the literature, the studies on this issue generally focused on the opinions of intern students or teachers and did not include the opinions of the instructors who conducted the teaching practice (Alptekin & Vural, 2014;Doğan & Güven, 2021;Özen et al, 2009;Polat, et al, 2020;Yıldırım-Yakar et al, 2021;Yücesoy-Özkan et al, 2019). In the studies conducted with intern students, it was found that some lecturers have positive characteristics such as being highly communicative, providing feedback, helping and understanding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teaching practice involves applying the theoretical knowledge gained during undergraduate education to a real-life teaching environment. It is essentially the process of preparing for and gaining experience in teaching, culminating in actual teaching experience (Paker, 2008;Yücesoy Özkan et al, 2019). Developing evaluation skills involves self-inquiry, identifying gaps in knowledge and skills, becoming aware of one's own teacher identity, and developing reflective thinking skills through participation in a teaching practice course (Collier, 1999;Freese, 1999;McDuffie, 2004;Poulou, 2007).…”
mentioning
confidence: 99%